Pemberdayaan Ekonomi Melalui Bazar UMKM di Desa Bangsring Dalam Membangun Kemandirian Desa Damai - Wulandari, Putri; Rachmawati, Sela; Abshor, Faqih Ulil; Kusumawati, Astrian; Najib, Ahmad Ainun (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to improve the knowledge and skills of MSMEs in business management, marketing, and digital technology in Bangsring Village. This activity was carried out through an MSME bazaar to increase community involvement through participatory programs, forming working groups or bazaar committees consisting of local residents and providing incentives for active community participation. The results of the community service activity show that the MSME bazaar program plays a strategic role in strengthening the local economy and building village independence. Through this bazaar, MSMEs are given the opportunity to market their products more widely, increase income, and establish sustainable partnerships..